Comparison of Bupivacaine versus Bupivacaine plus Dexamethasone in erector spinae plane block for post-thoracotomy analgesia. - Siddique, Dr Amjad; Dr. Sairah Sadaf; Dr. Sultan Ahmad (Medical Journal of South Punjab, 2024)
Objective: To compare the efficacy of bupivacaine alone and bupivacaine with dexamethasone in USG ESP block for post-thoracotomy analgesia. Methodology: In this Randomized Control Trial (RCT), thirty patients were registered and divided equally into groups "A" & "B". ESP Block was performed under general anesthesia at the end of the surgery. In group “A" an injection of Bupivacaine was used while in group “B”, dexamethasone was added to bupivacaine. The pain was recorded as Visual Analogue Scale(VAS) at the 1st, 6th, 12th, 24th & 36th Hours. Results: Mean VAS was higher in group “A” versus group "B" at the 12th hour, (3.4±1.4 v/s 0.4±1.12) respectively with P<0.001. Conclusion: In our study, we concluded that the combination of dexamethasone with bupivacaine in ESP Block not only provides better quality analgesia but also prolongs the duration of analgesia after thoracotomy. Clinical trial number: The Clinicaltrial.Gov registration number for our trial is NCT05277974. Keywords: Post-thoracotomy pain, Erector Spinae Plane Block, Bupivacaine, Dexamethasone.